The Role of Islamic Parenting in Building Self-Regulated Learning Ability for Early Children - Yuli salis hijriyani.; Fenty Andriani (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
Kemampuan anak dalam mengatur diri saat bermain seraya belajar kea rah proses proaktif dalam upaya untuk meningkatkan perkembangannya merupakan hal utama dalam penerapan self regulated learning (SRL). Dalam penerapannya dirumah dapat terjadi melalui pola asuh orang tua untuk mengintervensi anak menjadi pembelajar yang mandiri. Penelitian ini bertujuan untuk menjelaskan tentang peran pola asuh Islamic Parenting dan bagaimana peran pola asuh Islami dapat berhasil membangun kemampuan self regulated learning pada anak. Subyek penelitiannya adalah anak usia dini di Provinsi Jawa Timur. Jenis penelitian kualitatif dengan model analisis data Miles Huberman yaitu data direduksi sebagai upaya pemilihan data yang dibutuhkan dan display data setelah itu data diverifikasi untuk ditarik menjadi simpulan. Hasil penelitian yang diperoleh (1) Peran pola asuh Islamic Parenting merupakan suatu kesatuan utuh mulai dari sikap pengasuhan yang dilakukan orangtua pada anak dimulai sejak. dini, baik dalam membina, mendidik, hingga pada membiasakan, serta membimbing secara optimal berdasarkan Al-Qur’an dan Hadist (2) Keberhasilan pola asuh Islamic parenting dalam membangun Self regulated learning dapat terlihat pada kesiapan lingkungan belajar di keluarga, orang tua sebagai konseptor materi yang diberikan kepada anak seperti nilai-nilai akhlak pada kebiasaan sehari-hari, nilai akidah seperti pengenalan ciptaan Tuhan, dsb. Nilai edukasi bernuansa islami merupakan peran Islamic parenting sebagai upaya membangun hasil self regulated learning pada anak yang lebih optimal. Kata Kunci: Anak Usia Dini, Intervensi, Islamic Parenting, Orang Tua, Self Regulated Learning ABSTRACT. The ability of children to regulate themselves while playing and learning towards a proactive process in an effort to improve their development is the main thing in the application of self-regulated learning (SRL). In its application at home, it can occur through parenting parents to intervene children to become independent learners. This study aims to explain the role of Islamic parenting and how the role of Islamic parenting can successfully build self-regulated learning abilities in children. The research subjects were early childhood in East Java Province. This type of qualitative research uses Miles Huberman data analysis model, in which data is reduced as an effort to select the required data and display the data after that the data is verified to be drawn into conclusions. The research results obtained (1) The role of Islamic parenting style is a unified whole starting from the parenting attitude that is carried out by parents to children starting from. early, both in fostering, educating, getting used to, and guiding optimally based on the Al-Qur'an and Hadith (2) The success of Islamic parenting in building Self-regulated learning can be seen in the readiness of the learning environment in the family, parents as the conceptors material given to children such as moral values in daily habits, religious values such as the introduction of God's creation, etc. The educational value of Islamic nuances is the role of Islamic parenting as an effort to build more optimal results of self-regulated learning in children. Keywords: Early Childhood, Intervention, Islamic Parenting, Parents, Self-Regulated Learning